2019
DOI: 10.3390/jcm8030339
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Mechanisms of Action of Topical Administration of GLP-1 in an Experimental Model of Diabetic Retinopathy

Abstract: The main goals of this work were to assess whether the topical administration of glucagon-like peptide-1 (GLP-1) could revert the impairment of the neurovascular unit induced by long-term diabetes (24 weeks) in diabetic mice and to look into the underlying mechanisms. For that reason, db/db mice were treated with eye drops of GLP-1 or vehicle for 3 weeks. Moreover, db/+ mice were used as control. Studies performed in vivo included electroretinogramand the assessment of vascular leakage by using Evans Blue. NF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 31 publications
0
40
0
Order By: Relevance
“…GLP-1 agonists are indicated for improving glycemic control and reducing risk of major cardiovascular events in diabetes patients with established CV disease by impacting incretin regulation and insulin resistance (44,91). In a diabetic retinopathy rat model, topical administration of GLP-1 reverted the impairment of the neurovascular unit by exerting anti-inflammatory action, decreasing VEGF expression, promoting cell survival, and inducing neurogenesis (92). This intriguing data along with our new understanding of the multiple pathophysiologic mechanisms contributing to diabetes and its complications suggests that GLP-1 agonists could be beneficial in slowing and or preventing diabetic retinopathy in patients.…”
Section: Expanding the Armamentarium-broadening Our Approach To Treatmentioning
confidence: 89%
See 1 more Smart Citation
“…GLP-1 agonists are indicated for improving glycemic control and reducing risk of major cardiovascular events in diabetes patients with established CV disease by impacting incretin regulation and insulin resistance (44,91). In a diabetic retinopathy rat model, topical administration of GLP-1 reverted the impairment of the neurovascular unit by exerting anti-inflammatory action, decreasing VEGF expression, promoting cell survival, and inducing neurogenesis (92). This intriguing data along with our new understanding of the multiple pathophysiologic mechanisms contributing to diabetes and its complications suggests that GLP-1 agonists could be beneficial in slowing and or preventing diabetic retinopathy in patients.…”
Section: Expanding the Armamentarium-broadening Our Approach To Treatmentioning
confidence: 89%
“…Topical administration of GLP-1 and DPP-4 inhibitors prevented retinal neurodegeneration and vascular leakage in rodent models (92,114,117) The effect of DPP-4 inhibitor was thought to be due to prevention of GLP-1 degradation. Of note, GLP-1 retinal levels are significantly lower in patients with diabetes compared with controls (114).…”
Section: Treatment/prevention Of Neurodegenerationmentioning
confidence: 99%
“…90 Furthermore, a full-field flicker electroretinogram using a hand-held recording device has recently been successfully used for detecting early neurodysfunction in patients with diabetes without clinically detectable retinopathy, and has been related to HbA1c levels. 91 In addition, the recent experimental findings using drugs such GLP-1 92,93 or DPP-IV inhibitors, 94 which conferred both neuroprotection and prevention of vascular leakage open up a new scenario in which the screening for retinal neurodysfunction can be contemplated as critical for identifying the subset of patients in whom neuroprotective treatment might be of benefit.…”
Section: Screening For Retinal Neurodegenerationmentioning
confidence: 99%
“…One of them is the overproduction of free radicals and the consequent nitro-oxidative imbalance that leads to cell damage [5]. GLP-1 and GLP-1R agonists have emerged as potential drugs against DR due to their neuroprotective properties, but their effect on DR oxidative stress has not been assessed [1,3,13]. Herein, we provide evidence that an antioxidant effect can be added to the underlying mechanism by which GLP-1R agonists exert their beneficial action on the diabetic retina.…”
Section: Discussionmentioning
confidence: 91%
“…In recent years emerging evidence has indicated that glucagon-like peptide 1 (GLP-1) exerts beneficial effects in experimental diabetic retinopathy (DR) [1][2][3][4]. The underlying mechanisms involve a downregulation of vascular endothelial growth factor (VEGF), proinflammatory cytokines and proapoptotic signaling, reduction of the excitotoxicity mediated by glutamate and a protective role for the tight junctions and cells of the blood-retinal barrier [1][2][3][4]. However, little is known regarding he effect of GLP-1 on oxidative stress.…”
Section: Introductionmentioning
confidence: 99%